The Nightingale's Lament and Itys' Identity in Ovid's Metamorphoses - Sagal, Michal. (2017)
Abstract: The story of the nightingale has many versions, but these can be reduced to two plots from which the others grow. In the first, Aedon, married to Zethus, kills her son by accident. She intends to kill the oldest son of Niobe, who is married to the brother of Aedon's husband. In the second version, Procne kills her son to avenge the rape of her sister, Philomela, at the hands of Procne's own husband. The stories end in the same way: both mothers are transformed into a nightingale and lament their son Itys, singing his name eternally. In most versions of the story, Itys' identity is defined by the nightingale's lament. Ovid, however, suppresses the lament. The effect of this is to give Itys and his mother, Procne, identities that are separate from the nightingale's lament, and to give Itys a voice of his own.; Thesis (M.A.)--Tufts University, 2016.; Submitted to the Dept. of Classics.; Advisor: Marie-Claire Beaulieu.; Committee: Steven Hirsch, and Jennifer Eyl.; Keyword: Classical literature.